"It was the best worst day of my life": Narrative Content, Structure, and Process in Wisdom-Fostering Life Event Memories. (20th February 2018) - Weststrate, Nic M; Ferrari, Michel; Fournier, Marc A; McLean, Kate C
Abstract: Objectives: The purpose of this study was to examine laypeople's subjective understanding of their own wisdom development. To do this, autobiographical memories of wisdom-fostering life events were examined for (a) life-event characteristics, and (b) self-reflective processes believed to support growth in wisdom through life experience. Methods: Midlife adults ( N = 482) provided a written autobiographical memory of a wisdom-fostering life event. Memories were content analyzed by expert coders for life-event characteristics (i.e., fundamentality, emotional valence, cultural normativity, and specific event types) and self-reflective processes (i.e., narrative coherence, meaning-making, and personal growth). Participants also completed self-report and performance measures of wisdom. Results: Wisdom-fostering life events tended to be fundamental to life, culturally non-normative, and emotionally negative. Participants frequently reported developing wisdom from relationship events (e.g., interpersonal conflict, divorce) and life-threatening/mortality events (e.g., death, serious illness). Wisdom was positively associated with reconstructive (i.e., narrative coherence) and analytical (i.e., meaning-making, personal growth) components of self-reflection. Self-reflective processes varied as a function of life-event characteristics. Discussion: This study emphasizes the role of both persons and environments in the development of wisdom, and highlights the importance of self-reflection as a mechanism through which wisdom is constructed from life experience.